Desenvolvimento de nanocamadas e nanocristais de Óxido de Zircônio aplicados a catálise - Santos, Valdemir dos (Universidade Federal de São Carlos, 2007)
This work investigate the synthesis and characterization of a catalytic support of -alumina with a nanolayers and nanocrystals of ZrO2. The incorporation of the platinum began during and after the formation of the catalytic support. The technology is based on the Pechini method. The nanolayer was applied to cover the surface of the γ-alumina, avoiding a direct contact with the active phase (Pt). The structural and morphologic properties of these materials were analyzed through X ray diffraction, high resolution transmission electronic microscopy and zeta potential among anothers. It is found that surface reaction of alumina with zirconium (polimeric resin) leads to high dispersion of Zr. Degree of dispersion depends on several parameters such as heating treatment , zirconia cotent. Zirconia on alumina is atomically dispersed and forms only one phase in the range 10-25 wt% ZrO2. After this concentration level of ZrO2 crystallite are formed. Was observed that Pt present on catalytic support maintain high disperssion degree, this feature is independent of route used. The data analysis suggest that catalytic surface properties are different. Therefore, a particular catalytic behavior for these catalysts are expected.
Development of nanolayers and nanocrystals of Oxide of Zirconium applied the catalysis
Keywords: Físico-química; Potencial zeta; Partículas coreshell; Método de Pechini; Solução sólida; CIENCIAS EXATAS E DA TERRA::QUIMICA